Hydrogenation-Driven Phase and Morphology Changes in Ru-Doped TiO2 Nanotubes - Khorashadizade, Elham; Nasiri, Fatemeh (Fine Chemical Engineering, 2025)
A comprehensive understanding of the interplay between doping, thermal treatment, and structural evolution in titanium dioxide (TiO2) is critical for optimizing its performance in photocatalysis and energy applications. While doping and hydrogenation have been extensively studied as independent processes, their combined effects on the structural and morphological evolution of TiO2 nanotubes remain insufficiently explored. This study investigates the influence of hydrogenation temperature on ruthenium-doped TiO2 nanotubes (Ru-TNTs) subjected to heat treatment at 500 °C, 550 °C, and 600 °C under an Ar/H2 (90/10) atmosphere. Structural analysis reveals that increasing the hydrogenation temperature accelerates the anatase-to-rutile phase transition, induces lattice distortions, and promotes crystal growth, resulting in a reduction of the anatase phase fraction from 89.18% to 39.38%. High-resolution transmission electron microscopy (HRTEM) confirms these structural modifications, showing a transition from a well-defined crystalline lattice in Ru-TNTs hydrogenated at 500 °C to the formation of a disordered outer layer at 600 °C, consistent with X-ray diffraction (XRD) and field-emission scanning electron microscopy (FE-SEM) observations. Furthermore, microscopic analysis indicates significant morphological deformation with increasing temperature. These findings underscore the critical role of controlled hydrogenation in tailoring the structural and morphological properties of Ru-TNTs, providing valuable insights for the development of advanced materials with enhanced photocatalytic and energy conversion efficiencies.